ORGANIZATIONAL CLIMATE AND MANAGERIAL ABILITY, TEAMWORK, AND PERFORMANCE (Case Study at UPT Tahura Sultan Adam, Karang Intan District, South Kalimantan Province) - Fauziannor, Fauziannor (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to investigate the relationship between organizational climate, managerial ability, and teamwork on management performance in an organization. The background of this research is based on the recognition that the role of human resources (HR) in organizations is increasingly important and strategic in achieving organizational goals. Factors such as organizational climate, managerial ability, and teamwork are considered to influence employee performance. Through hypothesis testing, it was found that the results of organizational climate, managerial ability, and teamwork have a significant influence on management performance in organizations. The results of this study provide a further understanding of the importance of creating a good organizational climate, developing managerial skills, and strengthening teamwork in achieving optimal performance in an organizational context. The practical implications of this research are the need for more attention in managing the organizational climate, developing managerial capabilities, and developing teamwork to improve management performance.